Juridical Overview of Misappropriation of Medical Devices Procurement Budget By Hospitals - Leti Ratna Kusumawati; Zudan Arief Fakrulloh; Evita Isretno Israhadi (Publikasiku, 2023)
The existence of corruption in Indonesia is alarming, the increase in corruption cases has brought misery to the community so its existence must be eradicated. The Corruption Eradication Commission as the institution for eradicating corruption in Indonesia must be responsive and participate in supervising every activity related to budgeting for state needs, to ensure the actual realization of budgeting. Based on the Decree of the Head of the Madiun District Health Office Number: 188.45/1464/KPTS/402.102/2011, the judge considered that the actions taken by the defendant fulfilled all the elements of Article 3 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes in conjunction with Article 55 paragraph ( 1) item 1 of the Criminal Code (KUHP). Even though the Public Prosecutor charged the defendant with Article 2 of Law Number 20 of 2001, the Judge considered that the Public Prosecutor could not prove the